Free radicals run in lizard families. - Olsson, M; Wilson, M; Uller, T; Mott, B; Isaksson, C; Healey, M; Wanger, T (2008)
In the ageing individual, the production of reactive oxygen species (ROS) accelerates with cell senescence. Depending on the heritability of the underlying processes that determine net ROS levels, this may influence ageing per se and its evolutionary direction and rate of change. In order to understand the inheritance and evolution of net ROS levels in free-ranging lizards, we used flow cytometry together with ROS-sensitive fluorogenic probes to measure ROS in lizard blood cells. We measured basal levels of (i) non-specific ROS (superoxide, singlet oxygen, H2O2 and peroxynitrite), (ii) superoxide specifically and (iii) superoxide after CCCP treatment, which elevated ROS production in the mitochondria. The cumulative level of non-specific ROS was higher in adults than juveniles and superoxide level showed high heritability and variability among families. We suggest that the evolution of ROS dynamics may be ROS species specific and perhaps depend on the relative degree of uni- or biparental inheritance of ROS main regulatory pathways.